Evaluating Ground Beef Formulated with Different Fat Sources - Azlin Mustapha; Bryon R. Wiegand; Carol L. Lorenzen; Danielle R. Reynolds; Kathleen E. Shircliff; Zachary D. Callahan (Meat and Muscle Biology, 2019)
Objectives were to evaluate effects of fat source and formulated fat percentage on fatty acid composition, lean color stability, lipid oxidation, and aerobic microbial load during simulated retail display of ground beef patties. In Experiment 1 beef carcasses (n = 30) were chilled for 2 d and then fabricated. M. semimembranosus muscles were removed along with 2 fat sources (kidney and pelvic = KP and subcutaneous = S from the same carcass) and ground to achieve 75 and 95% lean. Fatty acid profile and thiobarbituric acid reactive substances (TBARS) were determined over a 7 d simulated retail display period. Saturated fat differed (P = 0.0004) by fat source, with KP having a higher percentage than S. Thiobarbituric acid reactive substances were higher for (P < 0.05) for patties made with S compared to KP. In Experiment 2 beef carcasses (n = 20), were fabricated and blended into ground beef as described in Experiment 1. After designated display time patties were removed and instrumental color measurement, myoglobin concentration, TBARS, and aerobic plate counts (APC) were collected. Oxymyoglobin (OMb) percentage decreased (P < 0.0001) by storage day and had source x formulated fat percentage interaction (P = 0.011). Inversely, storage day increased metmyoglobin (MMb) percentage (P < 0.0001) where d 1 < d 3 < d 5 < d 7, respectively. Changes in myoglobin form contributed to decreased a* values (P < 0.0001) over time. However, APC did not differ (P > 0.05) for d, fat source, or fat percentage. Discoloration in ground beef over 7 d of retail display was more a function of muscle pigment oxidation (OMb to MMb) than aerobic microbial spoilage.